IMPLEMENTASI KEBIJAKAN ZAKAT PROFESI (SUATU ANALISIS KOMPARATIF MENURUT HUKUM ISLAM DAN HUKUM POSISTIF) - Alhamid Baharudin (STISIPOL Mujahidin Buol, 2023)
Zakat is divided into two, namely soul zakat or zakat fitra and zakat property or zakat mal. Zakat mal is zakat imposed on assets owned by a person or institution with predetermined terms and conditions. The potential of these two zakat is very large if managed properly. In detail, the sunnah of the Prophet states that some of the assets that must be paid zakat, gold and silver, livestock, edible seeds, fruits and trade assets. This is a group of assets that must be issued zakat if the conditions have been fulfilled and have reached the nisab. However, with the times marked by the development of information technology, it has resulted in the emergence of various economic activities. The consequence of this development is the emergence of various types of income so that further studies are needed as a potential for zakat. In this regard, the description of this thesis departs from the problem of how to review Islamic law and positive law regarding professional zakat? And what are the similarities and differences of professional zakat according to a review of Islamic law and positive law? This study uses a normative juridical approach, data collection techniques that the author uses through library research which is better known as (library research) and uses direct and indirect quotations, in processing and analyzing data the author uses inductive, deductive and comparative methods. The results of the study show that income and income are a person's profession that generates large income in a relatively short time, so this type of profession is subject to/obliged to issue zakat in accordance with the legal basis of qiyas which has fulfilled its nisab. The similarity lies in the understanding, nisab, levels, haul and procedures for issuing zakat. While the location of the difference lies in legal certainty which still gives rise to differences of opinion.